Princípio do sigilo do doador do material genético versus princípio do conhecimento da origem genética - Bianchi, Beatriz Homem de Mello (2020)
The evolution of medicine, with the development of assisted human reproduction techniques, revolutionized the concept of the affiliation institute, which changed from a strictly legal criterion, based on marriage, to a biological one, and is currently based on a socio-affective criterion. In order to regulate the procedures resulting from assisted human reproduction, in view of the absence of rules in the Brazilian legal system in this regard, the Federal Council of Medicine issued Resolution No. 2,168/2017, which provides for confidentiality, in cases of heterologous assisted reproduction, of the donor of the genetic material, as a way of guaranteeing his identity against any liability of paternity, which must be attributed to people who have undergone assisted reproduction and want the parental project. Such a rule collides with another personality right, which is the knowledge of the genetic origin as conceived through heterologous assisted human reproduction. In view of the aforementioned collision, the present study, after a descriptive and comparative analysis between the species of norms, concludes that the referred personality rights are principles and that, in an eventual collision, the weighting technique should be used to solve them